Examining the Relationship between Environmental Health Conditions and the Incidence of Acute Respiratory Tract Infections (ARI) Among Students at San Roque Elementary School - Hoang, Vinh Nguyen; Tsholofelo, Ellen (Journal of Health Innovation and Environmental Education, 2026)
Purpose of the study: This study aimed to examine the relationship between environmental health conditions and the incidence of ARI among elementary school students. Methodology: An analytic observational study with a cross-sectional design was conducted among 80 students at San Roque Elementary School. Environmental health conditions were assessed using a structured observational checklist covering ventilation, sanitation, classroom density, waste management, and water availability. ARI incidence was determined through school health records and parental confirmation. Data were analyzed using Chi-square tests and multivariate logistic regression at a 95% confidence level. Main Findings: Of the observed classrooms, 40.0% were classified as having inadequate environmental health conditions. ARI prevalence among students was 36.3%. A significant association was identified between environmental health status and ARI incidence (p = 0.001). Students exposed to inadequate environmental conditions had 4.12 times higher odds of developing ARI (AOR = 4.12; 95% CI: 1.68–10.09; p = 0.002). Novelty/Originality of this study: This study advances prior research by operationalizing environmental health as a multidimensional composite construct within a real-world public elementary school setting, thereby generating context-specific empirical evidence linking structural environmental exposure to respiratory morbidity.